2015
DOI: 10.14740/ijcp225w
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Meningitis in a Child With Sickle Cell Anemia: A Case Report

Abstract: Children with sickle cell disease are mainly exposed to various infections, among which there is bacterial meningitis. We present a brief report of a pneumococcal meningitis, due to Streptococcus pneumoniae 33F, in a 3-year-old boy of African race with sickle cell anemia. He was vaccinated against Streptococcus pneumoniae with 13-valent vaccine, and he was also on antibiotic prophylaxis. The child has been successfully treated with cephalosporins for a complete duration of 6 weeks, while hospitalization lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently Chenou et al observed that SCD patients are 300 times more likely to develop bacterial meningitis than the normal population, and 10% of affected children die due to the infection generated by meningitis and pneumococcus [83]. Previous research found that meningitis in SCD patients caused by various bacteria, including H. influenzae, H. meningitis, and E. coli [84], and Streptococcus pneumonia, was responsible for 70% of bacterial meningitis cases in SCD children, while H. influenza was responsible for 80% [83,85]. The recurrence of meningitis occurs more frequently in SCD patients [86].…”
Section: Meningitismentioning
confidence: 99%
“…Recently Chenou et al observed that SCD patients are 300 times more likely to develop bacterial meningitis than the normal population, and 10% of affected children die due to the infection generated by meningitis and pneumococcus [83]. Previous research found that meningitis in SCD patients caused by various bacteria, including H. influenzae, H. meningitis, and E. coli [84], and Streptococcus pneumonia, was responsible for 70% of bacterial meningitis cases in SCD children, while H. influenza was responsible for 80% [83,85]. The recurrence of meningitis occurs more frequently in SCD patients [86].…”
Section: Meningitismentioning
confidence: 99%